Rekonstruksi Konsep Kepemilikan dan Pengelolaan Harta dalam Perspektif Akuntansi Syariah - Andi Kamilah Zahra; Imma Imma; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study discusses the reconstruction of the concept of ownership and management of assets in the perspective of Islamic accounting, which emphasizes that assets are a trust that must be managed ethically and oriented towards social welfare, not merely absolute ownership. The research uses a qualitative method based on literature study with an analytical-descriptive and critical-comparative approach, examining primary and secondary literature, regulations, and academic documents related to property ownership and management in Islam and Islamic accounting practices. The results show that the reconstruction of the concept of ownership emphasizes moral responsibility and fair distribution of benefits, while asset management requires transparency, efficiency, and sharia compliance, as reflected in the growth of sharia financial assets and SBN management in Indonesia. Practical implications include the development of a holistic reporting framework, more inclusive sharia accounting standards, and the role of accountants as moral and social supervisors. This study concludes that the reconstruction of the concept of assets is important for developing sharia accounting that is relevant, sustainable, and adaptive to modern economic dynamics.